Endogenous levels of cytokinins, indole-3-acetic acid and abscisic acid in in vitro grown potato: A contribution to potato hormonomics - Raspor, Martin; Motyka, Václav; Ninković, Slavica; Dobrev, Petre I; Malbeck, Jiří; Ćosić, Tatjana; Cingel, Aleksandar; Savić, Jelena; Tadić, Vojin; Dragićević, Ivana Č (Scientific reports, 2020)
A number of scientific reports published to date contain data on endogenous levels of various phytohormones in potato (Solanum tuberosum L.) but a complete cytokinin profile of potato tissues, that would include data on all particular molecular forms of cytokinin, has still been missing. In this work, endogenous levels of all analytically detectable isoprenoid cytokinins, as well as the auxin indole-3-acetic acid (IAA), and abscisic acid (ABA) have been determined in shoots and roots of 30 day old in vitro grown potato (cv. Désirée). The results presented here are generally similar to other data reported for in vitro grown potato plants, whereas greenhouse-grown plants typically contain lower levels of ABA, possibly indicating that in vitro grown potato is exposed to chronic stress. Cytokinin N-glucosides, particularly N7-glucosides, are the dominant cytokinin forms in both shoots and roots of potato, whereas nucleobases, as the bioactive forms of cytokinins, comprise a low proportion of cytokinin levels in tissues of potato. Differences in phytohormone composition between shoots and roots of potato suggest specific patterns of transport and/or differences in tissue-specific metabolism of plant hormones. These results represent a contribution to understanding the hormonomics of potato, a crop species of extraordinary economic importance.
Keywords: kyseliny indoloctové; Chromatography, High Pressure Liquid; Cytokinins; fyziologický stres; Tandem Mass Spectrometry; Solanum tuberosum; Plant Growth Regulators; Stress, Physiological; Plant Shoots; tandemová hmotnostní spektrometrie; Abscisic Acid; regulátory růstu rostlin; kořeny rostlin; výhonky rostlin; Indoleacetic Acids; kyselina abscisová; Plant Roots; vysokoúčinná kapalinová chromatografie; cytokininy